PRDX2 Protects Against Atherosclerosis by Regulating the Phenotype and Function of the Vascular Smooth Muscle Cell - Li, Jing; Wang, Cong; Wang, Wenjing; Liu, Lingzi; Zhang, Qingqing; Zhang, Jun; Wang, Bo; Wang, Shujing; Hou, Li; Gao, Chuanzhou; Yu, Xiao; Sun, Lei (Frontiers in Cardiovascular Medicine, 2021)
Peroxiredoxin 2 (PRDX2), an inhibitor of reactive oxygen species (ROS), is potentially involved in progression of atherosclerosis (AS). The aim was to explore the role and mechanism of PRDX2 in the AS. The expression of PRDX2 was evaluated in 14 human carotid artery tissues with or without AS. The results showed the positive reaction of PRDX2 was observed in carotid artery smooth muscle cells (CAVSMCs). To assess the mechanism by which PRDX2 may function in AS, CAVSMCs were transfected with pEX4-PRDX2 and si-PRDX2. The Catalase, ROS scavenger, was used to further confirm that PRDX2-induced inhibitory effects might be mediated through reducing ROS levels. Phenotype alteration and functional testing included transcription testing, immunostaining and expression studies. The drug of MAPK signaling pathway inhibitors SB203580, SP600125 and PD98059 were used to evaluate the underlying mechanism. In this study, we found that the protein level of PRDX2 and the level of peroxide were higher in human AS carotid artery tissues than in normal carotid artery tissues, accompanied with the activation of MAPK signaling pathway. Up-regulation of PRDX2 in the CAVSMCs significantly decreased the expression of ROS, COLⅠ, COL Ⅲ, VCAM-1 and ICAM-1 and inhibited the proliferation, migration and transformation of the CAVSMCs. Up-regulation of PRDX2 reversed the effect of CAVSMCs treated with tumor necrosis factor-α (TNF-α). In addition, PRDX2 down-regulation promoted the protein levels of p-p38, p-JNK, p-ERK, which was confirmed in relevant MAPK inhibitors treatment experiments. Our results suggest a protective role of PRDX2, as a scavenger of ROS, in atherosclerosis progression through inhibiting the VSMC phenotype alteration and function via MAPK signaling pathway.